Sraffian indeterminacy in general equilibrium revisited - Naoki Yoshihara; Se Ho Kwak (University of Massachusetts, Department of Economics, 2019)
In contrast to Mandler's (1999a; Theorem 6) impossibility result about the Sraffian indeterminacy of the steady-state equilibrium, we first show that any regular Sraffian steady-state equilibrium is indeterminate in terms of Sraffa (1960) under the simple overlapping generation economy. Moreover, we also check that this indeterminacy is generic. These results are obtained by explicitly defining a simple model of overlapping generation economies with Leontief production techniques, in which we also explain the main source of the difference between our results and Mandler (1999a; section 6).
Keywords: B51; D33; D50; 330; Sraffian indeterminacy